Host specificity of Metriona elatior, a potential biological control agent of tropical soda apple, Solanum viarum, in the USA - Medal, J. C.; Pitelli, R. A.; Santana, A.; Gandolfo, D.; Gravena, R.; Habeck, D. H. (Kluwer Academic Publ, 1999)
The leaf beetle Metriona elatior from Brazil-Argentina was screened in the Florida (USA) State quarantine facility as a potential biological control agent of tropical soda apple, Solanum viarum, a recently arrived weed species. Multiple-choice host-specificity tests were conducted in small cages (60 cm x 60 cm x 60 cm) using 95 plant species in 29 families. Adults fed heavily on the main target weed (S. viarum), and on turkeyberry, Solanum torvum (noxious weed of Asiatic origin); fed moderately on red soda apple, Solanum capsicoides (weed of South American origin), and eggplant, Solanum melongena (economic crop); and fed lightly on aquatic soda apple, Solanum tampicense (weed of Mexican-Caribbean-Central American origin), and on silverleaf nightshade, Solanum elaeagnifolium (native weed widely distributed). M. elatior adults laid 84 to 97% of their egg masses on S. viarum, and 3 to 16% on S. melongena. Non-choice host-specificity tests were also conducted in quarantine in which M. elatior adults and neonate larvae were exposed to 17 and 19 plant species, respectively. Tests with the neonates indicate that this insect was able to complete its development on S. viarum, S. torvum, S. melongena, and S. capsicoides. Although some adult feeding and oviposition occurred on S. melongena in quarantine on potted plants in small cages, no feeding or oviposition by M. elatior was observed in field experiments conducted in Brazil. Surveys in unsprayed S. melongena fields in Argentina and Brazil indicated that M. elatior is not a pest of S. melongena in South America. The evidence obtained from the South-American field surveys, Brazil open-field experiments, and Florida quarantine host specificity tests indicate that M. elatior causes significant feeding damage to S. viarum, and does not represent a threat to S. melongena crops in the USA. Therefore an application for permission to release M. elatior against S. viarum in the USA was submitted in October 1998.
Keywords: classical biological control; Solanaceae